Proximal myotonic myopathy: evidence for anticipation in families with linkage to chromosome 3q - Schneider-Gold, Christiane; Ziegler, A.; Ricker, K.; Grimm, T.; Kress, W.; Reimers, C. D.; Meinck, Hans-Michael; Reiners, K.; Toyka, K. V. (Neurology, 2000)
Objective: To investigate anticipation in proximal myotonic myopathy (PROMM). - Background: PROMM is a recently described autosomal dominantly inherited disorder similar to but distinct from myotonic dystrophy (DM). DM belongs to the group of inherited disorders with anticipation caused by an unstable trinucleotide repeat expansion. In PROMM, no mutation has been identified, although PROMM has recently been mapped to a gene locus on chromosome 3q. - Methods: We investigated 10 German families with the PROMM phenotype and linkage to chromosome 3q. We based our analysis of anticipation on the age of disease onset. Anticipation was assumed if the offspring had first symptoms earlier in life than his or her affected parent. For statistical analysis Independence Estimating Equations (IEE) and a Monte-Carlo bootstrap were used. - Results: In 27 affected living parent-offspring pairs from these 10 families, the mean difference of disease onset was 18.8 years with either statistical analysis (p < 10−14 and p < 10−15). The mean disease onset interval in years was greater in father-offspring as compared to the mother-offspring pairs (p < 0.05; IEE). - Conclusion: Our findings suggest the occurrence of anticipation in parent-offspring pairs from families with the PROMM phenotype and linkage to chromosome 3q. The different disease onset intervals in mother-offspring and father-offspring pairs could indicate a mild parent-of-origin effect. These observations are compatible with the suggestion that PROMM, like DM, may be a trinucleotide repeat associated disorder. In contrast to DM, anticipation in PROMM is milder, a congenital form does not seem to occur, and fertility does not appear to be affected.
Gesehen am 04.03.2021